Epigenetic mechanisms of TNFα activation in patients with endometrial cancer - Marichereda, V. G.; Rozhkovskaya, N. N.; Bubnov, V. V.; Bykova, N. A. (Journal of Education, Health and Sport, 2018)
Timely identification of risk groups, early signs of the disease onset and recurrence is an important aspect in management of endometrial cancer (EC) patients. There is an active search for early diagnosis new markers, detection of relapses and EC postoperative monitoring. Tumor necrosis factor alpha (TNFα) is a cytokine involved in the pathogenesis of various forms of cancer, as well as associated with chronic inflammation, obesity. The objective is to study TNFa gene methylation in EC and the possibility of its use as a marker for forecasting, monitoring, and EC risk development. Materials and methods. DNA methylation was determined by pyrosequencing in endometrial specimens taken from 10 patients with verified endometrial hyperplasia and 13 patients with EC when performing hysteroscopy with endometrial biopsy or endometrial curettage. Results and discussion. The total degree of methylation of the TNFα gene DNA promoter in the samples under study in the patients with simple and / or complex nonatypical endometrial hyperplasia was 62.6 ± 12.8%, which is higher than in EC patients (34.7 ± 8.8%). Conclusions. The results obtained showed the involvement of epigenetic mechanism associated with hypomethylation of the TNFα gene promoter, which can lead to the activation of the TNFα gene in EC. Determination of methylation DNA promoter of the TNFα gene and its amount can be used as a potential prognostic and diagnostic marker of EC.